Reflexões sobre as drogas como objeto de pesquisa histórica - Lima Dias, Luiza (Temporalidades, 2019)
In Brazil, many areas of research have been studying the topic of drugs, although State policies have historically looked almost exclusively for medicine’s perspectives to support their legislation and government actions regarding psychoactive substances. With the intention to present other perspectives to analyze the topic, this paper proposes a short historiographical contextualization of drugs. The paper problematizes the concept of “drug” itself – which can have many different meanings, often carrying a pejorative feature in its daily use – and exposes the necessity of humanities’ look at the discussion, considering that medical and scientific perspectives have historically dominated the debates, both in the academy and the public sphere.